Descrever os desfechos maternos, fetais e neonatais da Covid-19 em Mato Grosso–Brasil - Kubiszeski, Eloisa Helena (2022)
Severe Acute Respiratory Syndrome Coronavirus (COVID-19) (SARS-CoV-2) is an infection that manifests as mild symptoms to severe respiratory failure. Pregnancy can worsen the course of COVID-19 infection compared to non-pregnant women and indicate a greater likelihood of fatal complications associated with the disease, resulting in a high mortality rate and major neonatal complications. The present study describes the main maternal, fetal and neonatal outcomes of pregnant and postpartum women who were hospitalized and those who were followed up during prenatal, birth and postnatal care, after SARS-CoV-2 infection during pregnancy. Method: Composed of two studies, the first, a descriptive and retrospective study of the clinical and evolutionary characteristics of all pregnant and postpartum women hospitalized for COVID-19 from March 2020 to October 2021. The second, a prospective cohort study analyzing the maternal, fetal and neonatal outcomes of pregnant women with COVID-19, during the prenatal, delivery and postpartum period, from September 2020 to March 2022. All pregnant women with TR- Reactive PCR for SARS-COV-2, at any gestational age and, in this analysis, all pregnant women with pre-existing comorbidities and those lost to follow-up for various reasons were excluded. Thus, the study sample consisted of one hundred and thirty-two (132) patients. Both took place at the Júlio Muller University Hospital, in Cuiabá-MT/BR. Results: The main results found in pregnant and postpartum women with COVID-19 who were hospitalized presented the moderate and severe form of the disease. The main risk condition found was overweight/obesity and pre-gestational diabetes, arterial hypertension, asthma and autoimmune disease were the most prevalent comorbidities in the group. Elevated LDH, CRP and d-Dimer were relevant laboratory findings in this group of patients. The most frequent maternal outcomes were respiratory failure and invasive ventilatory support, thromboembolic events, sepsis and preterm labor. Maternal death occurred in 6.4% of pregnant and postpartum women. Prematurity and need for NICU were important complications for neonates. Stillbirth/neomortality occurred in 11.0%. In the second study, the cohort of pregnant women followed up during prenatal care, the main complications were: premature rupture of the membrane, preterm labor, postpartum hemorrhage and preeclampsia (at the end of pregnancy). The main fetal/neonatal complications were: small for gestational age (SGA), need for an intensive care unit (NICU) and fetal distress. The occurrence of COVID-19 during pregnancy increased the risk of maternal complications by 8.1 times in the second and 11.7 times in the third trimester, compared with the first trimester of pregnancy. For fetal/neonatal outcomes, risk 5.1 times and 18.1 times when COVID-19 occurred in the second and third trimesters, respectively, compared to the first trimester. Another factor associated with maternal and fetal complications was the clinical classification of COVID-19 as moderate/severe. Conclusion: It is concluded that clinical conditions at admission, associated with worse living conditions and lack of access to health care, result in an increase in the chances of severity and worsening of the outcomes of this group of women and neonates. The occurrence of COVID-19 during pregnancy increases the risk of maternal and fetal/neonatal complications, particularly if the infection occurs in the second or third trimester of pregnancy and if the infection progresses to a moderate/severe clinical classification of the disease. Therefore, increased surveillance is needed in pregnant women who have contracted SARCoV-2 at any time during pregnancy.